สภาวะที่เหมาะสมในการผลิตแท่งเชื้อเพลิงจากต้นข้าวโพดด้วยวิธีการพื้นผิวตอบสนอง - ศกลธน ราโชกาญจน์ (จุฬาลงกรณ์มหาวิทยาลัย, 2013)
The objective of this research was to study the optimum condition for fuel briquettes produced from corn stem using Response Surface Methodology (RSM). Corn stem was a waste from maize production and can be used as a raw material in the production of appropriate fuel for households and industries. The experiments were carried out into two parts. The first one was study the ratio of the corn stem, cob and binder from starch of cassava that gave the higher compressive strength of briquettes, and this briquettes must be had the weight of corn stem was high but the weight of cob and binder was low. The second one was study about temperature and time of carbonization that gave the briquettes had heating value and percent yield were high, and the carbonization must be used lowest temperature and time for reduce resource in production process of briquettes. The results showed that the appropriate in ratio of corn stem, cob and binder by weight was 7.5:1.5:2. This ratio was give the highest compressive strength was 0.3556 MPa and the density was 365.15 Kg/m3 respectively. And the appropriate of carbonization temperature was 475 degree Celsius and time was 90 minute. That gave the briquettes has heating value (4,689.43 Kcal/kg) and percent yield (40.20%) were high, the moisture content (5.54%) and ash content (7.45%) were low. But the total solids (94.46%), volatile solids (87.01%) and carbon content (48.34%) were high. From the optimum condition for fuel briquettes produced from corn stem using Response Surface Methodology (RSM). It was found that briquettes had the potential that could be developed for households and small industries.